Winnie-the-pooh : blood and honey [videorecording (Blu-Ray)] - Milne, A. A. (Alan Alexander), 1882-1956; Frake-Waterfield, Rhys; Dowsett, Craig David; Cordell, Chris; Doig-Thorne, Amber (Shout! Factory, 2024)
Enter the darkest corners of the Hundred Acre Wood. Five years ago, Christopher Robin abandoned his childhood companions, Winnie-the-Pooh and Piglet, and the woods in which they all played. Now an adult, Christopher has returned, with his fianceé Maria in tow, for a reunion with his old friends...only to find that in his absence, Pooh and Piglet have turned feral, silent...and murderous. What was once a joyous place of imagination and merriment becomes a violent battleground for survival in this audacious and terrifying spin on A.A. Milne's beloved children's stories.